EVALUATION OF LOCAL IMMUNE RESPONSE IN PREGNANT WOMEN WITH HUMAN PAPILLOMAVIRUS INFECTION - Musayeva, L.H.; Ismayilova, S.M. (World of Medicine and Biology, 2025)
This study investigated the impact of Human Papillomavirus infection on the local immune system during pregnancy. For this purpose, local immune responses – immunoglobulins and functional activity of neutrophils – in cervical secretions, were comparatively examined in three groups. Group I – 25 pregnant women with transient Human Papillomavirus infection, Group II – 24 pregnant women with persistent Human Papillomavirus infection, and a control group of 25 pregnant women without detected Human Papillomavirus infection. The results showed that, especially in cases of persistent Human Papillomavirus infection, although an increase in the total number of neutrophils in cervical mucus was observed, their phagocytic activity and functional capacity were significantly reduced. This is explained by the depletion of functional reserves of neutrophil cells due to the chronic course of the infection. At the same time, in persistent infections, the humoral immune response was found to be enhanced, with a statistically significant increase in IgG levels. This is interpreted as an indicator of the adaptive immune response developed against the prolonged presence of the virus in the body. The findings of this study demonstrate the potential diagnostic significance of local immune parameters – neutrophil activity and IgG levels – for predicting the clinical course and outcomes of Human Papillomavirus infection during pregnancy.